Targeted photodynamic therapy: enhancing efficacy through specific organelle engagement - Tao, Jiawen; Yuan, Zhifei; Zhou, Mengjiao (Frontiers in Pharmacology, 2025)
Photodynamic therapy (PDT) induces cancer cell death by utilizing photosensitizers to generate reactive oxygen species (ROS) upon light irradiation, which in turn trigger oxidative stress. However, the therapeutic efficacy of PDT is constrained by the short lifetimes and limited diffusion range of ROS, resulting in suboptimal outcomes and off-target effects. Specific organelle targeting, facilitated by rationally engineered photosensitizers and nanoplatforms with precise drug delivery capabilities that activate organelle-mediated cell death pathways, can maximize localized oxidative damage, enhance therapeutic efficacy, and minimize systemic toxicity. This review synthesizes advancements in organelle-targeted PDT, focusing on critical subcellular compartments (e.g., mitochondria, lysosomes, nuclei, cell membranes, ribosome, endoplasmic reticulum, golgi apparatus, autophagosome). It systematically summarizes the structural characteristics, design strategies, targeting mechanisms, and therapeutic effects of these organelle-targeted systems, with particular emphasis on organelle-mediated cell death signaling pathways. Ultimately, current challenges, prospective opportunities, and future research directions in organelle targeting are delineated, providing a strategic framework to advance organelle-targeted PDT toward precision therapy.